KONSTRIBUSI PEMIKIRAN DJALALUDDIN THAIB TERHADAP PENDIDIKAN AGAMA ISLAM DI MINANGKABAU - Ismael, Fauzan; Sesmiarni, Zulfani (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of writing this article is to examine Djalaluddin Thain's contribution to Islamic Religious Education in Minangkabau. H. Djalaluddin Thaib is someone who only has a "soerau" education, he has advanced in the fields of journalism, socio-economics, became the driving force for the unity of Islamic universities and eventually became the leader of the people's movement that rocked the atmosphere of political struggle in Indonesia. Jalaluddin Thaib's thoughts in the field of Islamic education are generally strategic in nature and are pioneering works, this was very rarely done by previous Islamic educators. This type of research is library research and data comes from several secondary and tertiary sources. literature related to Jalaluddin Thaib's thought and its relevance to modern education. This study is more focused on the attention and commitment of Jalaluddin Thaib in fighting for Indonesian independence and the development of Islamic education which can be seen further in several aspects of Islamic education thinking, including in terms of Islamic Education, goals, curriculum, teaching methods of educators. and Islamic Religious Education institutions.